Analysis of Students’ Epistemic Cognition Based on Cognitive Style in Mathematical Problem Solving - Ilmiah, Ilmiah; Cahya Mar'a Saliha Sumantri (COMPETITIVE: Journal of Education, 2025)
This study aims to describe students' epistemic cognition in solving mathematical problems reviewed from field independent and field dependent cognitive styles. This study uses a qualitative approach with a descriptive type of research. The subjects of the study were two students of class X of MA Abu Amr who were selected based on the results of the GEFT (Group Embedded Figures Test) test, with one student each with a field independent and field dependent cognitive style. Data were collected through mathematical problem-solving tests and interview guidelines, and then analyzed based on epistemic cognition indicators. The results showed that students with field-independent cognitive styles tended to have epistemic cognition at the rational dominant level. In contrast, field-dependent students showed a rational-empirical level of epistemic cognition. In conclusion, cognitive style affects the way students understand, process, and justify knowledge in solving mathematical problems. These findings show that there is a difference in the level of epistemic cognition based on students' cognitive styles, which can be taken into consideration in the development of learning strategies.